Influence of lean body mass distribution on ground reaction force and snatch performance in male and female weightlifters - Sihanath, W.; Ahn, N.; Papanek, P.; Kipp, K. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to determine the influence of lean mass distribution (LMD) on ground reaction forces (GRF) and snatch performance. Eighteen weightlifters completed dual x-ray absorptiometry scans and performed heavy snatch lifts on force plates. Leg and trunk LMD were correlated with snatch performance, but further analysis revealed that only leg LMD was a significant predictor for male weightlifters. GRF during the first pull were associated with performance for male weightlifters, while GRF during the second pull were more relevant for female weightlifters. Leg LMD was a strong predictor of GRF during both pulls with an emphasis on trunk LMD in females. These results showcase the interrelationships between LMD, GRF production, and snatch performance and provide insight on different determinants of performance in male and female weightlifters.